PLATELET PROTEINS FROM DIABETIC SUBJECTS CAUSE PHENOTYPIC CHANGES IN ENDOTHELIAL CELLS IN-VITRO: Life Sciences-Cell Biology - SERENE HILARY; SHAHNA S; JOTHYDEV KESAVADEV; ANUGYA BHATT (International Journal of Life Science and Pharma Research, 2022)
Diabetes is a chronic disease which is associated with platelet activation and endothelial dysfunction. Platelet endothelial interaction is the key regulator of the progression of cardiovascular diseases in diabetic subjects. Upon stimulation, platelets get activated and synthesize/secretes numerous proteins which are otherwise absent in the quiescent platelets. These proteins once in circulation may come in contact with underlying endothelial cells. Though there are several studies are being conducted to understand the mechanism of endothelium-platelet interaction in diabetes, effect of platelet releasates on endothelium remains untouched. In the present study we tried to explore the effect of platelet releasates on the endothelial cells by analyzing the cell viability, antithrombotic and prothrombotic markers in-vitro. The study was conducted with IEC approval. Eight diabetic subjects (test) were selected based on IDA definition and equal numbers of non diabetic controls were included in the study. Ten ml blood was collected from each subject. Activation status of platelets was studied by aggregometry, Scanning electron microscope and flowcytometry. Platelet releasates were incorporated into the fibrin growth factor composite matrix on which ECs were cultured. Apoptosis assay, morphological analysis, prothrombotic marker (von Willibrand Factor (vWF) and antithrombotic marker (endothelial nitric oxide synthase (eNOS), tissue plasminogen activator (tPA) were studied in cells exposed to test and control proteins. Data clearly indicated the hyperactivation of platelets in test group when compared to the control. vWF was found to be upregulated where as t-PA and eNOS were down regulated in test group thus confirming the phenotypic alteration of ECs towards prothrombotic. Diabetes is a major individual risk factor for the cardiovascular diseases and the two are bridged by platelet activation and endothelial dysfunction. This study showed the effect of platelet releasates to convert antithrombotic ECs to prothrombotic in nature which in-turn lead to the development of CVD in diabetic subjects.